Resurgence of interest in ostriches - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Ostrich farming has been practiced in South Africa for over 120 years but the modern expertise in farming them comes from the USA. Now Zimbabwean farmers are increasing their interest, expertise and production, and exports are expected to exceed 15...